Polyploid Induction Enhances Secondary Metabolite Biosynthesis in Clausena lansium: Morphological and Metabolomic Insights - Yu Ding; Liangfang Wu; Hongyao Wei; Zhichun Zhang; Jietang Zhao; Guibing Hu; Yonghua Qin; Zhike Zhang (Agriculture, 2025)
Polyploidy in plants can enhance stress resistance and secondary metabolite production, offering potential benefits for Clausena lansium (L.) Skeel, a medicinally valuable species. However, systematic studies of polyploidy-induced morphological, anatomical, and metabolic changes in this species are lacking. This study aimed to induce and characterize polyploid C. lansium lines, assess ploidy-dependent variations, and evaluate their impact on bioactive metabolite accumulation. Three cultivars were hybridized, treated with colchicine, and bred, yielding 13 stable polyploid lines confirmed by flow cytometry and chromosome counting. The polyploids exhibited distinct traits, including larger pollen grains, altered leaf margins, increased leaflet numbers, enlarged guard cells with reduced stomatal density, and thicker leaf tissues. Metabolomic analysis revealed that tetraploids accumulated significantly higher levels of flavonoids, alkaloids, and phenolic acids compared to diploids, while triploids showed moderate increases. These findings demonstrate that polyploidization, particularly tetraploidy, enhances C. lansium’s medicinal potential by boosting pharmacologically active compounds. The study expands germplasm resources and supports the development of high-quality cultivars for pharmaceutical applications.